2021
DOI: 10.3390/ijerph182111182
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushes as a Source of DNA for Gender and Human Identification—A Systematic Review

Abstract: Background: Few studies have reported the use of toothbrushes as a reliable source of DNA for human or gender identification. The present systematic review with the available information was conducted to answer the focus question “Is a toothbrush a reliable source of DNA for human or gender identification?”. Methods: The keyword combination “Toothbrush” and “DNA” was used to search databases including MEDLINE, Scopus, and Web of Science along with a manual search of reference lists of relevant articles. Duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The present study demonstrated that toothbrushes are a potential source of genetic material that could be explored further for the diagnosis of diseases which is concurrent with previous studies [29][30][31][32][33][34]. However, standardization is required with a larger sample size and yield of DNA and RNA with different time intervals of toothbrushing and storage conditions.…”
Section: Discussionsupporting
confidence: 85%
“…The present study demonstrated that toothbrushes are a potential source of genetic material that could be explored further for the diagnosis of diseases which is concurrent with previous studies [29][30][31][32][33][34]. However, standardization is required with a larger sample size and yield of DNA and RNA with different time intervals of toothbrushing and storage conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Higher scores represent a lower risk of bias. Other researchers have used these criteria to differentiate the quality of articles according to the AXIS tool (De Cock et al, 2022 ; Sujatha et al, 2021 ). Two reviewers performed the quality assessment separately and disagreements were resolved by consensus in the presence of a third reviewer.…”
Section: The Reviewmentioning
confidence: 99%
“…Higher scores represent a lower risk of bias. Other researchers have used these criteria to differentiate the quality of articles according to the AXIS tool (De Cock et al, 2022;Sujatha et al, 2021).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The current study is the first to perform gene profiling using used toothbrushes. Similar studies have used toothbrushes for person and gender identification, whereas gene profiling has not yet been performed [21,[30][31][32][33][34]. The methodology for DNA isolation has been standardized, and this study provides a reference for the future exploration of toothbrushes not only as a forensic tool but also for the early diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 99%